1938
DOI: 10.1021/ja01277a065
|View full text |Cite
|
Sign up to set email alerts
|

The Production of l-Erythrulose by the Action of Acetobacter suboxydans upon Erythritol

Abstract: Bacterial Production of /-Erythrulose 2507 creased by the addition of the magnesium sulfate.Group 11. The addition of inositol with Bios II does not give increased growth. This group includes strains Nos. 9, 11, 16 and 26. Group III. Growth is increased under the conditions given for Groups I and II. These include Nos. 7, 10, 18, 19, 22 and 41. The above data and groupings show that discrepancies in published results of bios studies may be due largely to differences in the strains of yeast employed and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1959
1959
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The optical rotation data for 3 was very similar to that reported by Bolte et [12] ). HPLC analysis of 5, and comparison to triacetylated l-erythrulose (l-erythrulose available commercially) indicated that 3 had been formed in 95% ee (S major isomer).…”
Section: Stereoselectivities Of Wt Ecoli Tksupporting
confidence: 87%
See 1 more Smart Citation
“…The optical rotation data for 3 was very similar to that reported by Bolte et [12] ). HPLC analysis of 5, and comparison to triacetylated l-erythrulose (l-erythrulose available commercially) indicated that 3 had been formed in 95% ee (S major isomer).…”
Section: Stereoselectivities Of Wt Ecoli Tksupporting
confidence: 87%
“…[5] With glycolaldehyde and non-a-hydroxylated substrates, although optical rotations have generally been reported, enantiomeric purities are not. [6] For example, when glycolaldehyde was reacted with 1 and spinach TK to give 3, the authors stated that the stereospecificity seems very high (optical rotation data [ [12] ), although the enantiomeric purity of the products was not fully assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Material in the medium containing radiotracer has not been identified but paper chromatography has excluded the presence of significant amounts of erythrose or erythrulose which might have been formed by the partial oxidation of erythritol as occurs with Acetobacter suboxydans (Whistler & Underkofler, 1938). Only small amounts of radiotracer were present in glucose and glycerol regions of autoradiograms, although large amounts of glycerol were excreted into the medium.…”
Section: Resultsmentioning
confidence: 99%
“…Thus a polyol with the D-erythro configuration (I) is oxidized mainly a t the secondary alcohol group adjacent to the terminal primary alcohol to give a ketose (11). Many examples of this reaction have been reported (3,4,5,6,7,8). More recently, cell-free extracts have been used for the oxidation of some polyols in an alkaline e~lvironment (optimum pH 7.8), although the reaction is less specific since polyols possessirlg either the L-threo-(111) or D-erythro-(I) configurations \vere utilized (9).…”
Section: Introductionmentioning
confidence: 99%